FACTORS OF HAPPINESS WILL AFFECT UNDERSTANDING OF ENTREPRENEURSHIP EDUCATION AMONG STUDENTS IN SECONDARY SCHOOL - Noorkartina Mohamad; Nor Musfirah Mohamad (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Entrepreneurship education is not only fostered at the tertiary level institutions but it has also been nurtured as early as the secondary school level in Malaysia. Regarding the awareness of the importance of entrepreneurship education, Malaysia have implemented subjects with elements of entrepreneurship in its education system, such as subjects’ accounting and business subjects. Therefore, this study proposes profiling those who are already taken the subject in school and examining the factors of understanding entrepreneurship education will reflect the level of happiness in their studies. A sample of 266 students from 13 secondary schools in Northern Malaysia are involved in this study The study’s findings indicate that more than half students understand and are happy with the entrepreneurial learning they have received and view business as an opportunity to involved.